A política externa enquanto guerra de posição: a inserção internacional do Brasil e o G20 financeiro - Castro, Gabriel Sandino de (2017)
The purpose of this master dissertation is to examine Brazil's performance in the financial G20. With the 2008 crisis, the G20 has become the most important forum for discussions in global political economy, as well as the participation of emerging countries in key issues in the development of the world economy. In short, we argue that it is possible to interpret Brazil's performance in the G20 as an attempt to develop a War of Position, a concept that originated in the thought of Antonio Gramsci. By rescuing this concept for the global political economy, Brazil's role in the financial G20 can be seen - except for some aspects - as an attempt by the Brazilian government to widen its deterrent power, considering the arrangements of world economic constraints and the difficulties structures of the economy Brazilian In this sense, we bring the War of Position as an interpretation of the strategy of the Brazilian government to raise the importance of Brazil in the world economic scenario. In fact, the present work aims to identify the instruments for Brazil's sovereign insertion in the G20 and to point out mechanisms used by the Brazilian government to expand its influence and increase dissuasive power.